Sugarcane Bagasse as the Source of Nanocrystalline Cellulose for Gelatin-Free Capsule Shell. (14th February 2022) - Sabara, Zakir; Mutmainnah, Alfirah; Kalsum, Ummu; Afiah, Irma Nur; Husna, Ismalia; Saregar, Antomi; Irzaman,; Umam, Rofiqul
Abstract : Gelatin-free capsules are possibly produced through an innovation which involves utilizing environmentally friendly materials derived from plants such as bagasse which are produced into nanocrystalline cellulose (NCC). This research was conducted to report the extraction and characterization of NCC from the abundant industrial plantation waste of sugarcane and its application as the base material for gelatin-free capsule shell material. The process involved using different concentrations of NCC at 1%, 2%, 4%, and 7% (in wt. %) with the addition of 1% hydroxypropyl methylcellulose (HPMC) (in wt. %) and 1% carbopol (in wt. %). Moreover, the NCC capsules obtained from sugarcane bagasse were tested for moisture content, tensile strength, elongation, solubility, and pH. The results showed that sugarcane bagasse contains 40–50% cellulose, 6.15%–9.5% moisture content which indicates they are potentially better in terms of storage, 7.25–7.85 pH, and 0.05–0.136 MPa gel strength, and the elongation value ranges from 7.19 to 87.51%. These values were discovered to have satisfied the standard requirements as indicated by the optimal concentration of 4% NCC +1% HPMC, which is in line with the Japanese Industrial Standard (JIS), thereby leading to the consideration of the material safe to be used as raw material in making capsule shells.